Blood, iron, & gold how the railroads transformed the world - Wolmar, Christian (Atlantic Books, 2010)
Christian Wolmar's biggest paperback yet. Blood, Iron and Gold tells the dramatic story of the people and events that shaped the world's railways and how the railways changed the world.